Low-dose Oral Vitamin K Reliably Reverses Over-anticoagulation due to Warfarin - Crowther, M. A.; Donovan, D.; Harrison, L.; McGinnis, J.; Ginsberg, J. (Thrombosis and Haemostasis, 1998)
Background: Patients receiving long-term warfarin frequently develop asymptomatic excessive prolongation of their international normalized ratio (INR) results. The most appropriate management strategy in these patients is unknown. This prospective cohort study was designed to address whether 1 mg of oral vitamin K effectively reduces the INR value of such patients. Methods: A prospective cohort study was performed in two tertiary care teaching hospitals, in which 62 patients receiving warfarin who had INR values between 4.5 and 10.0 received 1 mg of oral vitamin K. All patients had daily INR values and clinical assessments performed. Results: The mean INR value at presentation was 5.79 (95% confidence interval (CI) 5.48 to 6.09, range 4.5 to 9.5). Sixteen hours after receiving the 1 mg of oral vitamin K, the mean INR was 2.86 (95% CI 2.50 to 3.23). On the second and third days after vitamin K, the mean INR values were 2.20 (1.93 to 2.47) and 2.14 (1.85 to 2.44), respectively. No adverse events or bleeding complications were observed. In three patients (6%) the INR value rose between the time of vitamin K administration and the next INR determination; two patients received a further 2 mg dose of subcutaneous vitamin K. Conclusions: In patients receiving warfarin who have asymptomatic excessive prolongations in their INR results, 1 mg of oral vitamin K reliably reduces the INR to the therapeutic range within 24 h. This therapy is more convenient, less expensive, and might be safer than parenteral vitamin K. Thus, it should be considered in all non-bleeding patients receiving warfarin, who present with INR results of 4.5 to 9.5.Dr. Crowther is the recipient of a Medical Research Council of Canada Research Fellowship.Dr. Ginsberg is a Career Investigator of the Heart and Stroke Foundation of Ontario.